Análise de riscos ocupacionais nos campi da Fundação Oswaldo Cruz: um estudo de caso - Araujo, Solange Maria Ferreira de (2008)
The increasing activity of biomedical research and, by extension, the constant manipulation of microorganisms and materials with high potential of biological contamination turn the working/researching environment of the Fundação Oswaldo Cruz (FIOCRUZ) into a privileged locus for occupational hazards investigations. The present research displays a view of the activities developed in this Institution, describes its working environments, defining them according to occupational hazards from reports made by the Coordenação de Saúde do Trabalhador (CST) created by FIOCRUZ, and determines the number of the employees ruled by the Regime Jurídico Único in activity at the 21 Unities/Regional Centers in the years 2002, 2005 and 2007. It has as its main purpose to gather data that can be helpful in the discussion about the organizing criteria of reports adopted by the CST to grant additional payment to the employees and those reports determined by the Sistema Integrado de Saúde Ocupacional do Servidor Público Federal (SISOSP). Methodologically, the research adopts the case study, which has pointed to the following conclusions: (1) CST reports were made according to the law, through technical survey of all working environments to map the exact position of the employees, the activities deployed and the risk situations to which they were exposed, with their active participation, resulting in the inclusion of ergonomic hazards and accidents, although they were not accounted for by the law for the concession of additional payment; (2) given the nature of the activities developed by FIOCRUZ, it is established that its employees are seriously exposed to chemical, physical and biological, ergonomic and accident hazards, with high counts, according to the reports made by the CST; (3) during this research, our attention was drawn to the great number of female employees in the working environments, an aspect that was considered important as to the strategies to intervene in the processes that specifically affect the female worker s health. As to the criteria adopted by the SISOP to the making of reports, it was considered that they are insufficient specially because they do not take into consideration the active workers participation, leaving aside some particular aspects of the working environment. It is believed that this research has brought some contributions through the gathering of data that can recall some points about the workers health and the working particularities of the public employee in a broad sense